Development of an Embedded System for Use in Real-Time Intelligent Traps to Detecting Fruit Fly (Diptera:Tephritidae) - Santos, Gabriel; Silva, Vanessa; Moraes, Fabiano; Estrada, Emanuel; Rosa, Vagner (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
Fruit flies affect direct and indirect the fruit production, causing damage and losses in a worldwide scale. The control of fruit flies is usually done in an unregulated way, using insecticides in the form of bait-toxic, without knowledge of the infecting species. This work presents the development of an embedded system based on optoelectronic sensor to be used in an McPhail intelligent trap, sending remotely the data related to the fruit flies through a wireless protocol with low power consumption and wide range.